Testikelstörningar hos hingstar i Sverige - Engsäll, Ulrica (2011)
This project was initiated by a veterinarian, that at stallion performance tests for breeding during a number of years, noted breed differences in various types of testicular disorders. Therefore it was of interests to examine the proportion of testicular disorders within certain breeds. The aim with the project was in a first part to study cryptorchidism in common horse breeds in Sweden. Information about castrations of stallions performed during a 10 year period (2000-2009) was collected from computerized case records at five animal hospitals. The case records showed the numbers of castrations, normal cases and cases preformed on stallions with cryptorchidism, abdominal respectively inguinal. In a second part of the study information was collected considering testicular disorders from records of stallion performance tests, performed in Sweden during a five-year period. The summary of the case information from animal hospitals showed breed differences in Sweden regarding cryptorchidism. Cross breed horses (58%), Icelandic horse (43%) and Haflinger (33%) had the highest proportions of cryptorchism. The stallion performance test records showed also breed differences in testicular disorders. Generally, pony breeds had a higher frequency of testicular disorders than horse breeds. The fact that testicular disorders was more common among certain horse breeds than others indicate a genetic predisposition regarding stallion testicular disorders. It was not possible however to calculate incidences regarding testicular disorders for different horse breeds in Sweden. In order to get a better material for such an evaluation, improved control of the number of horses in Sweden is needed and also the possibility to collect information regarding the number of normal castrations that is carried out in Sweden in veterinary field practices.